2019
DOI: 10.1101/661306
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ESCRT machinery mediates selective microautophagy of endoplasmic reticulum

Abstract: ER‐phagy, the selective autophagy of endoplasmic reticulum (ER), safeguards organelle homeostasis by eliminating misfolded proteins and regulating ER size. ER‐phagy can occur by macroautophagic and microautophagic mechanisms. While dedicated machinery for macro‐ER‐phagy has been discovered, the molecules and mechanisms mediating micro‐ER‐phagy remain unknown. Here, we first show that micro‐ER‐phagy in yeast involves the conversion of stacked cisternal ER into multilamellar ER whorls during microautophagic upta… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…Moreover, it may enable therapeutic intervention in diseases associated with ER overload and aberrant lipid metabolism, such as diabetes and obesity. Besides organelle biogenesis, lipin activity impacts autophagy, axon regeneration, myopathy, dystonia, and neurodegeneration (Zhang et al , 2014; Grillet et al , 2016; Zhang & Reue, 2017; Fanning et al , 2019; Yang et al , 2019; Schäfer et al , 2020). Further unraveling the regulation of lipin will therefore have implications for a large variety of cellular processes and associated diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it may enable therapeutic intervention in diseases associated with ER overload and aberrant lipid metabolism, such as diabetes and obesity. Besides organelle biogenesis, lipin activity impacts autophagy, axon regeneration, myopathy, dystonia, and neurodegeneration (Zhang et al , 2014; Grillet et al , 2016; Zhang & Reue, 2017; Fanning et al , 2019; Yang et al , 2019; Schäfer et al , 2020). Further unraveling the regulation of lipin will therefore have implications for a large variety of cellular processes and associated diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In general, MVB is involved in nonselective autophagy. Recent studies have determined that MVBs can also participate in selective autophagy processes, such as the Cvt (cytoplasm‐to‐vacuole targeting) pathway and ER‐phagy (Huang et al ., 2014; Schafer et al ., 2020). The study found that the homologue of mammalian autophagy receptor NBR1‐Nbr1 interacts with two cytoplasmic hydrolases, Lap2 and Ape2, in a similar way to that observed in the Cvt signalling pathway and promotes their transport to the vacuole in yeast, which is called NVT (Nbr1‐mediated vacuolar targeting).…”
Section: Introductionmentioning
confidence: 99%
“…NVT elements colocalize with ESCRTs in multivesicular bodies (MVBs) and rely on ubiquitination for transport (Liu et al ., 2015). In yeast, the deletion of ESCRT‐0, ‐I, ‐II or ‐III protein, Bro1 or Vps4 can reduce or block endoplasmic reticulum autophagy (Schafer et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…ESCRT is involved in various cellular processes, including cytokinesis, plasma membrane repair, nuclear membrane repair, multivesicular body formation, vacuolar membrane repair, autophagosome formation, and microautophagy of the endoplasmic reticulum (11, 27, 28). Here, we find ESCRT in our screen for PMD response factors.…”
Section: Discussionmentioning
confidence: 99%